Prevalence and clinical characteristics of oral tori among outpatients in Northern Malaysia - K Sathya; Sham Kishor Kanneppady; T Arishiya (Journal of Oral Biology and Craniofacial Research, 2012)
ABSTRACT: Objectives: The objectives of this study were to determine the prevalence and clinical characteristics of torus palatinus (TP) and torus mandibularis (TM) in Malaysian dental patients. Methods: Thousand five hundred and thirty-two dental patients were examined for the presence of oral tori at the Faculty of Dentistry outpatient clinic, AIMST University. Factors such as race, age, sex, size, and shape of tori were studied. Results: The prevalence rates were 12% for TP and 2.8% for TM. A variation in the presence of tori among the three races in Malaysia–Chinese, Malays, and Indians–was noted, where the Chinese significantly had a higher prevalence of TP (17.9%) and TM (4.6%). Predominantly, tori were observed >40 years and older age group, and further both TP and TM were seen more commonly in women. Most TP were of smooth type (52.2%) and >2 cm (67.4%), while all TM were bilateral and nodular, plus most were <2 cm (67.4%). Conclusion: Presence of tori (TP and TM) was detected in 12.5% of the participants. The variations noted in the prevalence and clinical characteristics of tori among people of different races living in the same country reflect its multifactorial etiology. Both genetic and environmental factors are responsible for its occurrence, and particular races are more prone genetically where its expression is enhanced by environmental factors.